ظاهرة عقد الزَّواج الخارجيِّ في قانون الأحوال الشَّخصيَّة العراقيِّ: دراسة تحليلية - Alshekh, S.; Abdullah, R.; Samah, M. (Universiti Sains Islam Malaysia, 2024)
The research problem revolves around the extent to which this paper is able to account for the causes that lead to the spread of unofficial or illicit marriages in Iraq since the lawgiver has laid down the standards for official and legal marriage contracts in the Personal Status Law by recording such legal contracts in the competent courts. Hence, this paper will shed light on the effectiveness of the subsequent legal statement to curb this phenomenon. In fact, this legal statement, which is referred to in Article 10 (5) of the Iraqi Personal Status Law No. (188) for the year 1959, reads: "every man who holds a marriage contract out of court is subject to imprisonment for not less than six months, and not more than one year, or risk paying a fine of not less than three hundred dinars and not more than one thousand dinars. However, if he holds the contract out of court while he is still married to another woman, in this case, he is subject to imprisonment for not less than three years, and not more than five years." As a result, this paper will discuss the concept of out-of-court marriage, its categories, the causes of its commonness, the potential harms that it may inflict on the spouses and their children, and the extent to which this violates and break away from the legal objectives of Islamic law and the Iraqi Personal Status Law. In our analysis of the legal texts and judicial decisions issued by the personal status courts, we found that the Iraqi lawgiver was right to criminalize cases pertaining to of out of court marriages since they have harmful effects on both spouses in particular and society in general; and since the legal text is unable to limit the spread of this phenomenon, we see it as a prime necessity to call for the enactment of the law of the Marriage Official as an effective remedy to curb and limit the spread of illegal marriages